The emerging issue of cardiac dysfunction induced by antineoplastic angiogenesis inhibitors. (May 2013) - Tocchetti, Carlo G.; Gallucci, Giuseppina; Coppola, Carmela; Piscopo, Giovanna; Cipresso, Clemente; Maurea, Carlo; Giudice, Aldo; Iaffaioli, Rosario V.; Arra, Claudio; Maurea, Nicola
<x xml:space="preserve">Abstract</x> Left ventricular dysfunction from anticancer drugs has emerged as a relevant problem in the clinical and scientific communities. Anthracycline toxicity has always been the most relevant, but with the increasing use of biological targeted therapies in treatment protocols, with an increasing number of cancer survivors, new toxicities have been increasing in more recent years. Cardiomyopathy after ErbB2 inhibitors has been intensively studied. Another important class of biological anticancer drugs are vascular endothelial growth factor (VEGF) inhibitors. VEGF signalling is crucial for vascular growth, but it also has a major impact on myocardial function. Also, it is important to note that such angiogenesis inhibitors are multitargeted in most cases, and can produce a broad spectrum of cardiovascular side effects. Here we review the mechanisms and pathophysiology of the most significant cardiotoxic effects of antiangiogenic drugs, and particular attention is drawn to LV dysfunction, discussing the assessment and management on the basis of the most recent cardio‐oncological findings and heart failure guidelines.